Effect of Crocin From Saffron (Crocus sativus L.) Supplementation on Oxidant/Antioxidant Markers, Exercise Capacity, and Pulmonary Function Tests in COPD Patients: A Randomized, Double-Blind, Placebo-Controlled Trial - Hassan Ghobadi; Hassan Ghobadi; Nasim Abdollahi; Hanieh Madani; Mohammad Reza Aslani; Mohammad Reza Aslani (Frontiers Media S.A., 2022)
Background: Chronic obstructive pulmonary disease (COPD) is a progressive and chronic respiratory disorder characterized by reversible airflow limitation and lung parenchyma destruction. The main feature of COPD is inflammation and disturbance of the oxidant/antioxidant balance in the airways. The therapeutic use of herbal supplements with antioxidant and anti-inflammatory properties seems to be very useful in the medical management of patients with COPD.Method: COPD patients were divided into placebo and intervention groups (each group n = 23) in a clinical trial study. The intervention group received crocin supplementation (30 mg/day for 12 weeks), and the control group received a placebo. Pre- and after the intervention, pulmonary function tests (PFTs), exercise capacity (using a 6-min walking distance test (6MWD)), and serum levels of total oxidant status (TOS), total antioxidant capacity (TAOC), and NF-kB were assessed using the ELISA test.Results: Intervention with crocin for 12 weeks in COPD patients decreased serum levels of TOS and NF-κB as well as increased TAOC. In addition, the results of the 6MWD test reveal an improvement in patients' exercise capacity.Conclusion: Crocin supplementation appears to effectively establish oxidant/antioxidant balance and improve inflammatory conditions in patients with COPD.